Gross anatomy and histology of the alimentary system of Characidae (Teleostei: Ostariophysi: Characiformes) and potential phylogenetic information - Alonso,Felipe (2015)
A compared study of the morphology of the alimentary tract and liver of seven selected species corresponding to the main clades of the Characidae family is presented herein. Three new set of characters corresponding to 1) alimentary tract gross anatomy, 2) alimentary tract histology and 3) liver gross anatomy are evaluated as potential sources of data for future phylogenetic studies of the Characidae. Not considerable interspecific variation was observed at the histological level and therefore this source is not considered to be phylogenetically informative at the taxonomic level analyzed. In contrast, liver and alimentary tract gross anatomy presented important interspecific variation while a relatively homogenous intraspecific morphology was observed. Those characters are optimized in tree-topologies from previous phylogenetic analyses and their evolution and potential relationship with ecological traits are discussed.